Imaging characteristics associated with failure of nonoperative management in high-grade pediatric blunt renal trauma. Issue 5 (October 2016) - Au, J.K.; Tan, X.; Sidani, M.; Stanasel, I.; Roth, D.R.; Koh, C.J.; Seth, A.; Gargollo, P.C.; Tu, D.; Gonzales, E.T.; Smith, T.G.; Janzen, N.
Summary: Introduction: Some children who sustain high-grade blunt renal injury may require operative intervention. In the present study, it was hypothesized that there are computed tomography (CT) characteristics that can identify which of these children are most likely to need operative intervention. Materials and methods: A retrospective review was performed of all pediatric blunt renal trauma patients at a single level-I trauma center from 1990 to 2015. Inclusion criteria were: children with American Association for the Surgery of Trauma (AAST) Grade-IV or V renal injuries, aged ≤18 years, and having available CT images with delayed cuts. The CTs were regraded according to the revised AAST grading system proposed by Buckley and McAninch in 2011. Radiographic characteristics of renal injury were correlated with the primary outcome of any operative intervention: ureteral stent, angiography, nephrectomy/renorrhaphy, and percutaneous nephrostomy/drain. Results: One patient had a Grade-V injury and 26 patients had Grade-IV injuries. Nine patients (33.3%) underwent operative interventions. Patients in the operative intervention cohort were more likely to manifest a collecting system filling defect ( P = 0.040) (Fig. A) and lacked ureteral opacification ( P = 0.010). The CT characteristics, including percentage of devascularized parenchyma, medial contrast extravasation, intravascular contrast extravasation, perirenal hematoma distance and laceration location, were not statistically significant. Of the 21 patients who had a collecting system injury, eight (38.1%) needed ureteral stents. Renorrhaphy was necessary for one patient. Although the first operative intervention occurred at a median of hospital day 1 (range 0.5–2.5), additional operative interventions occurred from day 4–16. Thus, it is prudent to closely follow-up these patients for the first month after injury. Two patients with complex renal injuries had an accessory renal artery resulting in well-perfused upper and lower pole fragments, and were managed nonoperatively without readmission (Fig. B). Conclusions: Collecting system defects and lack of ureteral opacification were significantly associated with failure of nonoperative management. A multicenter trial is needed to confirm these findings and whether nonsignificant CT findings are associated with operative intervention. In the month after renal injury, these patients should be mindful of any changes in symptoms, and maintain a low index of suspicion for an emergency room visit. For the physician, close follow-up and appropriate counseling of these high-risk patients is advised. Figure A. Axial CT image demonstrating left renal pelvis extravasation and collecting system filling defect (blue arrow). B. Coronal CT image demonstrating dual arterial supply of right kidney with lower pole accessory artery (*) and well-perfused upper and lower pole fragments. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)